Relationship Between Family Support and Adherence to Antiretroviral Medication in Patients with HIV at Bhayangkara Hospital, Indramayu, Indonesia - Wenny Nugrahati Carsita; Julisah Rusyani; Alvian Pristy Windiramadhan Windiramadhan; Ridho Kunto Prabowo Prabowo (Babali Nursing Research)
Introduction: Adherence to antiretroviral (ARV) treatment is one of the most critical factors in the successful management of HIV patients. Family support significantly influences treatment adherence, as family members are closest to the patient and are expected to provide motivation and monitor adherence to ARVs. This study aimed to determine the relationship between family support and ARV adherence among HIV patients.